2019
DOI: 10.1002/alr.22289
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between systemic inflammatory response and quality of life in patients with chronic rhinosinusitis

Abstract: Background Local sinonasal inflammation resulting from altered T‐cell immune signaling is a contributor to the pathogenesis of chronic rhinosinusitis (CRS). CRS patients experience negative impacts on quality of life (QOL) and suffer from comorbidities linked to systemic inflammation. However, systemic inflammatory profiling to evaluate the association between systemic inflammation and QOL in CRS has not been performed. Our objectives were to compare local and systemic inflammatory gene expression in patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Both studies found that distinct biomarkers were associated with disease‐specific and/or general quality of life scores. Orb et al . additionally found that local and systemic inflammatory gene expression correlates with clinical markers of disease severity.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Both studies found that distinct biomarkers were associated with disease‐specific and/or general quality of life scores. Orb et al . additionally found that local and systemic inflammatory gene expression correlates with clinical markers of disease severity.…”
mentioning
confidence: 98%
“…Chowdhury et al . and Orb et al . assessed mucus cytokines and expression of genes involved in T‐cell immune signaling, respectively.…”
mentioning
confidence: 99%
“…One explanation would be the fact that with age there is an immune vulnerability due to various comorbidities, and on the other hand there is a cumulative effect of inflammatory, infectious or non-infectious phenomena over time. Regarding the gender difference, it is probably due to the high prevalence of smokers over female smokers [ 10 ].…”
Section: ⧉ Discussionmentioning
confidence: 99%
“…Tissue specimens were either immediately frozen and stored at −80°C until being subjected to mRNA extraction and gene expression analysis, or fixed in 4% neutral formalin for 48 hours until being subjected to tissue processing by the Molecular Diagnostics Core at the Huntsman Cancer Institute (Salt Lake City, UT) and protocols for immunohistochemical analysis, as previously detailed. 29 , 30 …”
Section: Methodsmentioning
confidence: 99%
“…mRNA extraction and multiplex gene expression analysis were performed as previously reported. 29 , 30 Briefly, after being thawed at 4°C, ethmoid tissues were placed in 0.6 mL of lysis buffer containing 5-mm stainless-steel beads and homogenized using a Qiagen Tissuelyser LT (Qiagen; Hilden, Germany). Nucleic acid was extracted using a Qiagen AllPrep RNA microRNA Universal Kit and a QiaCube, following the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%